Implementation of Social Forestry Program in The Form of Community Forestry : Case Study of Tunas Muda Forest Farmer Group in Saenam Village, West Miomaffo Sub-District, North Central Timor District - Wulan Chairunissa Anwar; Wilhelmina Seran; Nixon Rammang (Journal of Scientech Research and Development, 2024)
Social Forestry is a sustainable forest management system implemented in the State Forest Area or Rights Forest/Customary Forest with the aim of improving community welfare. One of the villages involved in social forestry activities under the Community Forest scheme since 2017 is Saenam Village. Therefore, it is necessary to conduct research to find out the implementation of Community Forestry. The research objective is to determine the level of success and realization of the Saenam Village Community Forest. The type of research used is qualitative research with the basic method of descriptive research, and the determination of samples using non-random sampling techniques. The success of the Community Forest in Saenam Village has not been successful when viewed from the income of farmers. However, the community obtained benefits including access rights to manage and carry out activities in the forest area. The realization of Community Forest activities has not been fully realized, because there are still technical obstacles in the implementation of Community Forest management in the field, such as the lack of assistance, supervision and monitoring by the forest management unit, lack of training on Community Forest management and there is still no mapping of individual work areas.